Shelf Life Study of Pedada Fruit Jam (Sonneratia caesolaris) With The Addition of Carrageenan: - - Visakhadevi, Jelena; Andriyono, Sapto; Yuli Pujiastuti, Dwi (Journal of Marine and Coastal Science, 2024)
Pedada fruit (Sonneratia caseolaris) contains phytochemicals such as steroids, tripenoids and flavonoids. Phytochemical compounds are antioxidants that neutralize free radicals that attack body cells. The application of making pedada fruit jam with the addition of carrageenan can function as a natural preservative. The purpose of this study was to determine the effect of adding carrageenan to the shelf life of pedada fruit jam. The research treatment consisted of 0 week of storage (P0), 1 week (P1), 2 weeks (P2), 3 weeks (P3), and 4 weeks (P4). Parameters observed in this study were the total plate count test, viscosity test, and antioxidant activity test with spektrofotometer Uv-Vis. The data obtained was tested with the ANOVA statistical test and continued with the DMRT test. The results of the research show that antioxidant activity and viscosity have decreasing values with each storage period, while microbiological activity is inversely proportional to antioxidant activity and viscosity, namely with increasing values with each storage period. The storage time for pedada fruit jam with the addition of carrageenan had a significant effect on antioxidant activity, viscosity and microbiological activity which had significantly different values (p < 0.05).